Gancidin W, A Diketopiperazine as Promising Antimalarial Agent Isolated from Endophytic Streptomyces 10 - Baba, Mohd Shukri; Abu Hassan, Zainal Abidin; Latip, Jalifah; Edrada-Ebel, RuAngelie; Mohamad Zin, Noraziah (2014)
It was undeniable fact that falciparum malarial was reported remained to be resisted against nearly all current antimalarial drugs. On top of that, endophytic Streptomyces strains are potential sources for novel bioactive molecules. In this study, a type of diketopiperazine, namely Gancidin W (GW) or prolylleucyldiketopiperazine (C11H18O2N2) which was fractionated from broth culture of Streptomyces SUK10, living endophytically in the bark of Shorea ovalis tree was in-vivo tested against Plasmodium berghei NK65 in male ICR strain mice. GW exhibited an inhibition rate of nearly 80% at 6.25 and 3.125 μg kg-1 body weight on day four using the 4-day suppression test method on male ICR strain mice. Comparing GW at both concentrations with quinine hydrochloride and normal saline as positive and negative controls, respectively, 50% of the mice treated with 3.125 μg kg-1 body weight managed to survive for more than 11 months after infection, which almost reached the life span of normal mice. Biochemical tests of selected enzymes and proteins in blood samples of mice treated with GW were also within normal levels; in addition, no abnormalities or injuries were found on internal vital organs.As in-vitro toxicity assessment of GW on the blood enzymes were also investigated, these promising findings indicated that those compounds isolated from endophytic Streptomyces SUK 10 may be potentially contributed for extracting a new substance in medicinal field for antimalarial treatment with no human undesired effects.